Antimicrobial Properties of Homo Fermenting Lactic Acid Bacteria (LAB) Isolated from Kunu-Zaki (A Spontaneously Fermenting Nigerian Cereal Beverage) - S. O. Oluwajoba; F. A. Akinyosoye; V. O. Oyetayo (Research Perspectives of Microbiology and Biotechnology Vol. 3, 2024)
Aim: The present study aimed to determine the antibiotic reaction and adhesion pattern of antimicrobial homo-fermenting LAB strains in the fermenting slurries of kunu-zaki, Nigeria. Background: Lactic acid bacteria are usually found in decomposing plants and lactic products. Lactic acid is the major metabolic end-product of the carbohydrate fermentation. LAB is a large group of fermentative, anaerobe aero-tolerant microorganisms that are usually present in the gut of humans and other animals, raw vegetables, meat and meat products, and cereal. Study Design: Samples were obtained directly from the 72-hour fermenting mash of the kun-uzaki made from each cereal type. The Pour plate technique was used to isolate the organisms. The pure colonies isolates were examined according to their colony morphology, catalase reaction and gram reaction. Inhibition of indicator lawn used \(≥\)10mm inhibition as antibiotic susceptible. Adhesion was measured by staining and quantifying grains of Digitariaexilis (acha), Sorghum bicolour (sorghum) and Pennisetum americanum (millet) in composite and non-composite proportions. LAB isolates were obtained on MRS agar. Homo-fermenting isolates were identified at species level using the API 50 CHL test kit. Antibiotic sensitivity testing on the identified isolates followed the modified standard Kirby-Bauer procedure on MRS agar (pH 7.4) using the disc diffusion technique with selected antibiotics. For quality control of the antibiotics, sensitive reference strains S. aureus ATCC 25923 and E. coli ATCC 25922 obtained from the Nigeria Institute of Medical Research were used. Adhesion properties were determined by differential staining of the bacterial cells that bound to intestinal epithelial cells as observed under light and phase contrast microscopy. Results: Antimicrobial substances produced by the eight LAB isolates inhibited the growth of four selected human pathogens in vitro. All eight LAB isolates were resistant to amoxicillin, gentamycin and ciprofloxacin. L. plantarum126, L. paracasei sub sp paracasei339 and Pediococcus damnosus32 were resistant to erythromycin whilst all others were susceptible. L. plantarum126 and L. paracaseisubspparacasei339 were resistant to all antibiotics tested. All LAB isolates demonstrated high in-vitro intestinal epithelial cell adhesion potential. The result of this study documents findings on the antibiotic resistance pattern of these eight homo-fermenting lactic acid bacteria present in ready to drink kunu-zaki. If these homo-fermenting strains are to be used in kunu-zaki as starter cultures, it is important that they should be further carefully examined for inability to transfer antibiotic resistance genes to food pathogens. Conclusion: When used in conjunction with these antibiotic treatments, kunuzaki may not have an impact on the antibacterial activity of LAB. To ensure that these LAB strains cannot pass antibiotic resistance genes to food pathogens, they must be thoroughly screened if they are to be used as kunu-zaki starter cultures.